Pyeloplasty in children by lumbotomy approach using infant feeding tube as single stent - Amit Singh; Minu Bajpai; Manisha Jana (Wolters Kluwer Medknow Publications, 2014)
Background: The objective of this study was to assess the outcome in children who had undergone pyeloplasty by lumbotomy approach using infant feeding tube (IFT; 5 Fr) as a single stent. Materials and Methods: During January 2000 and December 2010, 134 pyeloplasty were performed by the lumbotomy approach. The procedure involves single layer anastomosis at pelvi-ureteric junction using vicryl 5-0/6-0 (reduction of pelvis if required). An IFT 5 Fr with multiple holes used as a single stent to serve as nephrostomy and as transanastomotic stent also. Results: There were 109 males and 25 females with M: F ratio of 4.3:1. Left-side pelvi-ureteric junction obstruction (PUJO) was seen in 117 (87.3%) while right side PUJO in 17 (12.7%). Mean age of presentation was 52.7 months (range 9-120 months). Postoperative complications included infection 2 (1.5%), urinoma formation 1 (0.7%), urine leak 3 (2.2%), non drainage 2 (1.5%), accidental removal of the stent 2 (1.5%). Follow-up scan done at 3 and 9 months showed improved drainage in 124 (92.5%), preserved renal function in 129 (96.2%) cases. Overall success rate 97.5%. Conclusion: Transanastomotic stent using IFT not only provide an effective drainage but also avoid the complications associated with double-J stents and nephrostomies, with the added benefit of being cheaper and availability.